Improving Students' Learning Motivation Using Project Based Learning Models by Optimizing Technology Through Video Media in History Subjects - Putra, Patman Adi; Ilmiawan, Ilmiawan; Dwinawanti, Dyna Esthi; Iksan, Iksan; Wijayanti, Kristina Elis (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research aims to increase students' learning motivation using the Project Based Learning (PJBL) model by optimizing technology through video media. The method used in this research is Classroom Action Research with a descriptive qualitative approach. The subjects of this research were 30 students in class XI 1 of SMA Negeri 1 Kayangan. This explains that optimizing the use of video media technology in learning can increase students' learning motivation as seen from the implementation of learning as seen from the results of observations and evaluations in cycle II. Based on the evaluation results of students who achieved the Minimum Completeness Criteria (KKM), namely before implementing the PjBL learning model, there were 12 students out of the total number of students with an average percentage of 73.83%. Meanwhile, after implementing the PjBL learning model, there was an increase reaching an average percentage of 84.33%, consisting of 26 students who had reached the KKM.